2021
DOI: 10.3390/electronics10060702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Augmented Reality Object and Texture Presentation on Walking Behavior

Abstract: Wearable devices that display visual augmented reality (AR) are now on the market, and we are becoming able to see AR displays on a daily basis. By being able to use AR displays in everyday environments, we can benefit from the ability to display AR objects in places where it has been difficult to place signs, to change the content of the display according to the user or time of day, and to display video. However, there has not been sufficient research on AR displays’ effect on users in everyday environments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…(1) In the future, we will verify various people to generalize our findings to a wider attribute of people since the number of subjects was about 10 and the subjects of this experiment were young university students. On the other hand, since the previous study (Adams et al, 2015;Isoyama et al, 2021) focusing on psychological phenomena of information presentation systems showed the necessary verification results with about 10 people, we consider that our experiment also obtained the necessary verification results to understand and discuss our focused effect.…”
Section: Future Studysupporting
confidence: 54%
“…(1) In the future, we will verify various people to generalize our findings to a wider attribute of people since the number of subjects was about 10 and the subjects of this experiment were young university students. On the other hand, since the previous study (Adams et al, 2015;Isoyama et al, 2021) focusing on psychological phenomena of information presentation systems showed the necessary verification results with about 10 people, we consider that our experiment also obtained the necessary verification results to understand and discuss our focused effect.…”
Section: Future Studysupporting
confidence: 54%
“…Therefore, we will verify various and many people to generalize our findings to wider attributes of people. On the other hand, we consider that our experiment also obtained the necessary verification results to understand and discuss our focused effect since the previous study [9,71] focusing on psychological phenomena of information presentation systems showed the necessary verification results with about 10 people. (3) Verification of activities to which the proposed method can be applied: we will verify whether the proposed method can be applied to the memorization of various learning domains and the memorization tasks of daily activities.…”
Section: Limitations and Future Workmentioning
confidence: 64%
“…Perhaps the most obvious question in relation to the adopted paradigm is: Why shadows? There are many other environmental characteristics that one may choose to manipulate, such as spatial consistency ( Warren, 2019 ; Muryy & Glennerster, 2021 ) or texture composition ( Isoyama, Sakuragi, Terada, & Tsukamoto, 2021 ). My motivation for manipulating shadows stems from the pivotal role played by this scene component in formulating early theories of biological image reconstruction ( Gibson, 1979 ; Marr, 1982 ).…”
Section: Discussionmentioning
confidence: 99%